Niemiecka chadecja wobec konfliktu rosyjsko-ukraińskiego - Bielawska, Agnieszka (Wydział Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2015)
Niniejszy artykuł ma na celu prześledzenie stanowisk polityków niemieckiej chadecji wobec konfliktu rosyjsko-ukraińskiego oraz wpływu, jaki wywarli na działania Unii Europejskiej i Federacji Rosyjskiej. Przedstawia szeroki wachlarz opinii i komentarzy polityków chadeckich od¬nośnie politycznego i gospodarczego zbliżenia Ukrainy z Unią oraz kryzysu na Ukrainie w okresie od listopada 2014 r. do czerwca 2015 r.

This paper presents the positions of German Christian Democrat politicians towards the Russian-Ukrainian conflict and the impact they exert on the activities of the European Union and the Russian Federation. It presents a wide range of opinions and comments of Christian Democrat politicians regarding the political and economic rapprochement of Ukraine with the EU and the crisis in Ukraine between November 2014 and June 2015.
German Christian-Democrats towards the Russian-Ukrainian conflict
Keywords: CDU/CSU; Ukraina; Federacja Rosyjska; Unia Europejska; konflikt; CDU/CSU; Ukraine; Russian Federation; European Union; conflict